(untitled) (Modern Problems of Metallurgy, 2020)
The present state of smelting of ferrosilicon manganese due to the deterioration of the quality of manganese concentrates is characterized by low extraction of manganese, silicon and an increase in the slag multiplicity. This requires the improvement of smelting technology with the use of charge materials with high reactivity, which is ensured by their preliminary preparation for melting. One method of preparation may be the method of mechanical activation of components separately or joint activation to provide high rates of the degree of recovery of elements in the metal phase. In order to attract mechanically activated fine materials for smelting of si-licomanganese, the basic technological requirements of preliminary preparation of briquetting briquette are grounded. Using hydrolysis lignin as a binder provides strong briquettes. At pressing pressures of 450-550 kg/cm2, the strength of the raw braces is 65-68 kg/cm2, and the fired in a reducing atmosphere at temperatures up to 1000оС, the strength reaches 160-185 kg/cm2. The study of the kinetics of joint carbon-thermal reduction of manganese and silicon at temperatures of 1250-1600 ° C with continuous weight loss control of the charge batch shows that the degree of recovery of the fractured, mechanically activated charge is 1.5 - 1.8 times higher than the reproducibility of the charge component 3- 0 mm and 2-3 times higher than the degree of recovery of the factory charge. Based on the results of chemical analysis of the experimental metal samples, it is shown that the application of mechanical activation in the joint processing of the mixture is significantly higher characteristics of extraction of manganese in the alloy by reducing the pre-formation of the slag phase and the recovery in this case of manganese from the slag melt